Breakdown of 3-(allylsulfonio)propanoates in bacteria from the Roseobacter group yields garlic oil constituents - Chhalodia, Anuj Kumar; Dickschat, Jeroen S. (Beilstein Journal of Organic Chemistry, 2021)
Two analogues of 3-(dimethylsulfonio)propanoate (DMSP), 3-(diallylsulfonio)propanoate (DAllSP), and 3-(allylmethylsulfonio)propanoate (AllMSP), were synthesized and fed to marine bacteria from the Roseobacter clade. These bacteria are able to degrade DMSP into dimethyl sulfide and methanethiol. The DMSP analogues were also degraded, resulting in the release of allylated sulfur volatiles known from garlic. For unknown compounds, structural suggestions were made based on their mass spectrometric fragmentation pattern and confirmed by the synthesis of reference compounds. The results of the feeding experiments allowed to conclude on the substrate tolerance of DMSP degrading enzymes in marine bacteria.
Keywords: Allium sativum; allyl sulfides; 3-(dimethylsulfonio)propanoate; Roseobacter; volatiles

(untitled) - Wertheim, T. (Ann. Chem. Pharm., 1844)

(untitled) - Semmler, F. W. (Arch. Pharm. (Weinheim, Ger.), 1892)

(untitled) - Cavallito, C. J.; Buck, J. S.; Suter, C. M. (J. Am. Chem. Soc., 1944)

(untitled) - Shang, A.; Cao, S.-Y.; Xu, X.-Y.; Gan, R.-Y.; Tang, G.-Y.; Corke, H.; Mavumengwana, V.; Li, H.-B. (Foods, 2019)

(untitled) - Block, E.; Ahmad, S.; Jain, M. K.; Crecely, R. W.; Apitz-Castro, R.; Cruz, M. R. (J. Am. Chem. Soc., 1984)

(untitled) - Stoll, A.; Seebeck, E. (Helv. Chim. Acta, 1948)

(untitled) - Stoll, A.; Seebeck, E. (Helv. Chim. Acta, 1949)

(untitled) - Block, E. (Angew. Chem., Int. Ed. Engl., 1992)

(untitled) - Brodnitz, M. H.; Pascale, J. V.; Van Derslice, L. (J. Agric. Food Chem., 1971)

(untitled) - Segev, E.; Wyche, T. P.; Kim, K. H.; Petersen, J.; Ellebrandt, C.; Vlamakis, H.; Barteneva, N.; Paulson, J. N.; Chai, L.; Clardy, J.; Kolter, R. (eLife, 2016)

(untitled) - Barak-Gavish, N.; Frada, M. J.; Ku, C.; Lee, P. A.; DiTullio, G. R.; Malitsky, S.; Aharoni, A.; Green, S. J.; Rotkopf, R.; Kartvelishvily, E.; Sheyn, U.; Schatz, D.; et al. (Sci. Adv., 2018)

(untitled) - Kessler, R. W.; Weiss, A.; Kuegler, S.; Hermes, C.; Wichard, T. (Mol. Ecol., 2018)

(untitled) - Schulz, S.; Dickschat, J. S. (Nat. Prod. Rep., 2007)

(untitled) - Dickschat, J. S. (Nat. Prod. Rep., 2017)

(untitled) - Dickschat, J. S.; Wagner-Döbler, I.; Schulz, S. (J. Chem. Ecol., 2005)

(untitled) - Dickschat, J. S.; Reichenbach, H.; Wagner-Döbler, I.; Schulz, S. (Eur. J. Org. Chem., 2005)

(untitled) - Thiel, V.; Brinkhoff, T.; Dickschat, J. S.; Wickel, S.; Grunenberg, J.; Wagner-Döbler, I.; Simon, M.; Schulz, S. (Org. Biomol. Chem., 2010)

(untitled) - Dickschat, J. S.; Rabe, P.; Citron, C. A. (Org. Biomol. Chem., 2015)

(untitled) - Todd, J. D.; Rogers, R.; Li, Y. G.; Wexler, M.; Bond, P. L.; Sun, L.; Curson, A. R. J.; Malin, G.; Steinke, M.; Johnston, A. W. B. (Science, 2007)

(untitled) - Curson, A. R. J.; Rogers, R.; Todd, J. D.; Brearley, C. A.; Johnston, A. W. B. (Environ. Microbiol., 2008)

(untitled) - Todd, J. D.; Curson, A. R. J.; Dupont, C. L.; Nicholson, P.; Johnston, A. W. B. (Environ. Microbiol., 2009)

(untitled) - Todd, J. D.; Curson, A. R. J.; Kirkwood, M.; Sullivan, M. J.; Green, R. T.; Johnston, A. W. B. (Environ. Microbiol., 2011)

(untitled) - Curson, A. R. J.; Sullivan, M. J.; Todd, J. D.; Johnston, A. W. B. (ISME J., 2011)

(untitled) - Todd, J. D.; Kirkwood, M.; Newton-Payne, S.; Johnston, A. W. B. (ISME J., 2012)

(untitled) - Sun, J.; Todd, J. D.; Thrash, J. C.; Qian, Y.; Qian, M. C.; Temperton, B.; Guo, J.; Fowler, E. K.; Aldrich, J. T.; Nicora, C. D.; Lipton, M. S.; Smith, R. D.; et al. (Nat. Microbiol., 2016)

(untitled) - Howard, E. C.; Henriksen, J. R.; Buchan, A.; Reisch, C. R.; Bürgmann, H.; Welsh, R.; Ye, W.; González, J. M.; Mace, K.; Joye, S. B.; Kiene, R. P.; Whitman, W. B.; et al. (Science, 2006)

(untitled) - Reisch, C. R.; Stoudemayer, M. J.; Varaljay, V. A.; Amster, I. J.; Moran, M. A.; Whitman, W. B. (Nature, 2011)

(untitled) - Brock, N. L.; Citron, C. A.; Zell, C.; Berger, M.; Wagner-Döbler, I.; Petersen, J.; Brinkhoff, T.; Simon, M.; Dickschat, J. S. (Beilstein J. Org. Chem., 2013)

(untitled) - Brock, N. L.; Menke, M.; Klapschinski, T. A.; Dickschat, J. S. (Org. Biomol. Chem., 2014)

(untitled) - Ansede, J. H.; Pellechia, P. J.; Yoch, D. C. (Environ. Sci. Technol., 1999)

(untitled) - Dickschat, J. S.; Zell, C.; Brock, N. L. (ChemBioChem, 2010)

(untitled) - Burkhardt, I.; Lauterbach, L.; Brock, N. L.; Dickschat, J. S. (Org. Biomol. Chem., 2017)

(untitled) - Grob, K.; Zürcher, F. (J. Chromatogr., 1976)

(untitled) - Ansorena, D.; Astiasarán, I.; Bello, J. (J. Agric. Food Chem., 2000)

(untitled) - Kubec, R.; Drhová, V.; Velíšek, J. (J. Agric. Food Chem., 1998)

(untitled) - Ansorena, D.; Gimeno, O.; Astiasarán, I.; Bello, J. (Food Res. Int., 2001)

(untitled) - Bonaïti, C.; Irlinger, F.; Spinnler, H. E.; Engel, E. (J. Dairy Sci., 2005)

(untitled) - Zoghbi, M. d. G. B.; Andrade, E. H. A.; Maia, J. G. S. (Flavour Fragrance J., 2002)

(untitled) - Mnayer, D.; Fabiano-Tixier, A.-S.; Petitcolas, E.; Hamieh, T.; Nehme, N.; Ferrant, C.; Fernandez, X.; Chemat, F. (Molecules, 2014)

(untitled) - Hahnke, S.; Brock, N. L.; Zell, C.; Simon, M.; Dickschat, J. S.; Brinkhoff, T. (Syst. Appl. Microbiol., 2013)

(untitled) - Beaulieu, J. C.; Grimm, C. C. (J. Agric. Food Chem., 2001)

(untitled) - van Den Dool, H.; Dec. Kratz, P. (J. Chromatogr., 1963)

(untitled) - Yang, C.; Jin, Q.; Zhang, H.; Liao, J.; Zhu, J.; Yu, B.; Deng, J. (Green Chem., 2009)